Identification of common antigens of three pathogenic Nocardia species and development of DNA vaccine against fish nocardiosis. Issue 95 (December 2019) - Chen, Jianlin; Tan, Wanchun; Wang, Wenji; Hou, Suying; Chen, Guoquan; Xia, Liqun; Lu, Yishan
Abstract: Fish nocardiosis is a chronic granulomatous bacterial disease and three pathogens have been reported so far, including Nocardia asteroids, N. seriolae and N . salmonicida . However, the absence of antigen markers is a bottleneck for developing effective vaccines against fish nocardiosis. In this study, the antigenicity of whole-cell protein of these three pathogenic Nocardia species were profiled by immunoproteomic analysis and 7 common immunogenic proteins were identified as follows: molecular chaperone DnaK (DnaK), molecular chaperone GroEL (GroEL), 30 S ribosomal protein S1 (RpsA), TerD family protein (TerD), FHA domain-containing protein (FHA), 50 S ribosomal protein L7/L12 (RplL) and PspA/IM30 family protein (PspA). Furthermore, the DNA vaccine encoding FHA gene against fish nocardiosis was developed and its efficacy was investigated in hybrid snakehead. The results suggested that it needed at least 7 d to transport pcDNA-FHA DNA vaccine from injected muscle to head kidney, spleen and liver and stimulate host's immune system for later protection. In addition, non-specific immunity paraments (serum lysozyme (LYZ), peroxidase (POD), acid phosphatase (ACP), alkaline phosphatase (AKP) and superoxide dismutase (SOD) activities), specific antibody (IgM) titers production and immune-related genes ( MHCIα, MHCIIα, CD4, CD8α, IL-1β and TNFα ) were used to evaluate the immune response induced in pcDNA-FHA vaccinated hybrid snakehead, it proved that all these mentioned immune activities were significantly enhanced after immunization. The results also showed hybrid snakehead vaccinated with pcDNA-FHA had higher survival rate (79.33%) compared with the controls after challenge with N. seriolae, indicating that the pcDNA-FHA DNA vaccine can supply immune protection against N. seriolae infection. Taken together, this study may warrant further development of these common immunogenic proteins as the antigens for vaccine or diagnosis and facilitate the prevention and treatment of fish nocardiosis. Graphical abstract: Image 1 Highlights: The antigenicity of whole-cell protein of three pathogenic Nocardia species ( Nocardia serioale, N. asteroids, N. salmonicida ) were profiled by immunoproteomic analysis. The 7 common immunogenic proteins of three pathogenic  Nocardia  species were identified. A DNA vaccine was prepared by applying one of the common immunogenic proteins (FHA) as antigen.